THE EFFECT OF THE RELEVANCE OF THE VALUE OF ACCOUNTING INFORMATION AND GOOD CORPORATE GOVERNANCE ON STOCK PRICES WITH COMPANY SIZE AS A MODERATION VARIABLE - Nurul Ulfa; Holiawati; Nofryanti (International Journal of Accounting, Management, Economics and Social Sciences (IJAMESC), 2025)
This study aims to empirically investigate the impact of the value relevance of accounting information and Good Corporate Governance (GCG) on the stock prices of Indonesian banking companies. Furthermore, it examines the moderating role of firm size in these relationships within the dynamic context of the post-PSAK 71 regulatory environment. Utilizing a quantitative associative design, this research employs a balanced panel data methodology. The sample consists of 24 banks listed on the Indonesia Stock Exchange (IDX) from 2020 to 2024, yielding 120 firm-year observations. Value relevance is proxied by Earnings Per Share (EPS), GCG is measured by a dummy variable reflecting compliance with OJK guidelines, and firm size is measured by the natural logarithm of total assets. The Random Effects Model (REM), selected through Chow, Hausman, and Lagrange Multiplier tests, is used for hypothesis testing alongside Moderated Regression Analysis (MRA). The results indicate that the value relevance of accounting information (EPS) has a significant positive effect on stock prices, supporting Signaling Theory. Conversely, Good Corporate Governance (GCG) does not exhibit a significant direct effect on stock prices. Notably, firm size significantly strengthens the relationship between value relevance and stock price. However, it does not moderate the relationship between GCG and stock price. This study provides timely empirical evidence from the Indonesian banking sector following the implementation of PSAK 71. It contributes to the literature by clarifying the contingent role of firm size, demonstrating that it amplifies financial signals but not governance signals, thus offering a nuanced understanding of value relevance and governance in an emerging market context.